2023
DOI: 10.1017/s1478951523000548
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with death literacy among Swedish adults: A cross-sectional exploratory study

Abstract: Objectives Death literacy is a recent conceptualization representing both individual and community competence, for example, a set of knowledge and skills for engaging in end-of-life-related situations. Little is yet known about which factors are associated with death literacy. A cross-sectional survey using the Swedish version of the Death Literacy Index, the DLI-S, was therefore conducted to explore associations between death literacy and sociodemographic, health, and experience variables. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Furthermore, death literacy-the knowledge and understanding of end-of-life and death care options-has previously been shown to be positively influenced by being widowed and lived experiences of end-of-life care and death, both informal and formal through professional or volunteer work. 35 The bereaved family members' Original research preferences for place of care at the end of life, place of death and what is most important in end-of-life care are most likely influenced by their increased death literacy through their experiences as family members of a severely ill and dying person.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, death literacy-the knowledge and understanding of end-of-life and death care options-has previously been shown to be positively influenced by being widowed and lived experiences of end-of-life care and death, both informal and formal through professional or volunteer work. 35 The bereaved family members' Original research preferences for place of care at the end of life, place of death and what is most important in end-of-life care are most likely influenced by their increased death literacy through their experiences as family members of a severely ill and dying person.…”
Section: Discussionmentioning
confidence: 99%
“…Scores were calculated by summing items and scaling by the number of items in a subscale (with a range of scores between 0 and 10). The DLI was tested and validated in Australia, the United Kingdom, Turkey, and Sweden (Abacigil et al 2019;Graham-Wisener et al 2022;Johansson 2022;Johansson et al 2023). The authorizations to use the GDI and the DLI in this study were obtained from the authors.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…The findings in our study also highlighted that closeness with parents is positively correlated to an individual's level of death literacy. Research has shown that families with strong parent-child relationships tend to have higher levels of death literacy among adult children after experiencing the death of their parents (Johansson et al 2023), implying that experiencing the death of parents could be a learning process, particularly for those with close relationship with parents, in which one could develop a better understanding and acceptance of death through open communication and emotional support among family members. It can be seen that the inclusion of family support plays an essential role in achieving a good death.…”
Section: Relationship With Parents Is Important For Death Literacymentioning
confidence: 99%